Male mice are susceptible to high fat diet-induced hyperglycaemia and display increased circulatory retinol binding protein 4 (RBP4) levels and its expression in visceral adipose depots. (1st January 2016) - GV, Asha; M, Raja Gopal Reddy; M, Mahesh; A, Vajreswari; SM, Jeyakumar
Abstract: Vitamin A and its metabolites are known to modulate adipose tissue development and its associated complications. Here, we assessed the vitamin A status and its metabolic pathway gene expression in relation to sexual dimorphism by employing 35 days old C57BL/6J male and female mice, which were fed either stock or high fat (HF) diet for 26 weeks. HF diet feeding increased body weight/weight gain and white adipose tissue (WAT) of visceral and subcutaneous regions, however, increase in vitamin A levels observed only in subcutaneous WAT. Further, the expression of most of the vitamin A metabolic pathway genes showed no sexual dimorphism. The observed HF diet-induced hyperglycaemia in male corroborates with increased retinol binding protein 4 (RBP4) levels in plasma and its expression in visceral adipose depots. In conclusion, the male mice are susceptible to high fat diet-induced hyperglycaemia and display higher plasma RBP4 levels, possibly due to its over-expression in visceral adipose depots.